Broad-spectrum bioactivities of a sulfated heteropolysaccharide from Bacillus tequilensis MYG163: antioxidant, anti-Inflammatory, anticancer, antimicrobial, and antibiofilm properties - Maha Abdullah Alwaili; Mohammed A. Alshehri; Thanaa R. Abdulrahman; Faisal Miqad K. Albaqami; Abdullah Alghamdi; Mona Othman I. Albureikan; Taghreed Shamrani; Abdullah Albelasi; Mohammad El-Nablaway; Samy Selim; Ahmed Ghareeb (Journal of Taibah University for Science)
A novel exopolysaccharide (EPS-R1) from the Red Sea bacterium Bacillus tequilensis MYG163 was isolated and characterized. The strain produced 6.33 g/l of EPS-R1, which was identified as a sulfated heteropolysaccharide containing uronic acid, N-acetyl glucose amine, and various monosaccharides. EPS-R1 showed strong antioxidant properties (>80% in DPPH and ABTS assays) and anti-inflammatory effects on COX-1 (IC50 = 25.74 µg/mL) and COX-2 (IC50 = 48.57 µg/mL). While safe for normal cells, it demonstrated cytotoxicity against colon (IC50 = 203.25 µg/mL) and pancreatic cancer cells (IC50 = 122.99 µg/mL). The compound effectively inhibited Candida albicans (MIC = 15.62 µg/mL) and showed superior antibacterial activity compared to gentamicin against Enterococcus faecalis (33 mm vs. 30 mm) and Klebsiella pneumoniae (42 mm vs. 17 mm). It significantly reduced bacterial biofilm formation (86-88% inhibition at 75% MBC) and Candida biofilms (60-90% reduction). These diverse bioactivities suggest EPS-R1's potential as a therapeutic agent.